Role of Lys335 in the metastability and function of inhibitory serpins - Im, H; Yu, MH (CAMBRIDGE UNIV PRESS, 2000)
The native form of inhibitory serpins (serine protease inhibitors) is not in the thc thermodynamically most stable, state but in a metastable staler which is critical to inhibitory functions. To understand structural basis and functional roles of the native metastability of inhibitory serpins, we have been characterizing stabilizing mutations of human alpha(1)-antitrypsin. a prototype inhibitory serpin. One of the sites that has been shown to be critical in stability and inhibitory activity of alpha(1)-antitrypsin is Lys335. In the present study, detailed roles of this lysine were analyzed by assessing the effects of 13 different amino acid substitutions. Results suggest that size and architect of the side chains at the 335 site determine the metastability of alpha(1)-antitrypsin. Moreover, factors such as polarity and flexibility of the side chain at this site, in addition to the metastability, seem to be critical for the inhibitory activity. Substitutions of the lysine at equivalent positions in two Other inhibitory serpins, human alpha(1)-antichymotrypsin and human antithrombin III. also increased stability and decreased inhibitory activity toward alpha-chymotrypsin and thrombin, respectively. These results and characteristics of lysine side chain, such as flexibility, polarity, and the energetic cost upon burial, suggest that this lysine is one of the structural designs in regulating metastability and function of inhibitory serpins in general.
Keywords: PLASMINOGEN-ACTIVATOR INHIBITOR-1; REACTIVE CENTER LOOP; INFLUENZA HEMAGGLUTININ; CONFORMATIONAL CHANGE; HINGE REGION; HUMAN ALPHA(1)-ANTITRYPSIN; PROTEINASE COMPLEX; CRYSTAL-STRUCTURE; HEPARIN-BINDING; MECHANISM